A Nova Paróquia: os desafios pertinentes à criação, formação e administração numa perspectiva de “comunidade de comunidades” - Alves, Rodrigo Fernando (2017)
In recent years, the Catholic Church has addressed the theme of the parish and reflected on the need for its renewal to become "New Parish" - especially after V CELAM (Document of Aparecida), Apostolic Exhortation Evangelii Gaudium by Pope Francis and of Document 100 published by the Brazilian Bishops' Conference (CNBB). This dissertation deals with the creation, formation and administration of the New Parish in the spirit of the Second Vatican Council and post-conciliar ecclesial developments in order to be a "community of communities". The conversion proposal reaches all stages of the New Parish from birth to maturity. The first chapter discusses the creation of the New Parish, comparing how parishes and dioceses were erected in Brazilian history with current proposals - such as: considering the reality and demands of the people and the region, expanding the spaces for dialogue, to focus on the improvement of the evangelizing activity as a criterion, to seek help in the human and social sciences, etc. The vision that must lead this process is that of the disciple-missionary. In addition, the implementation of the New Parish depends directly on the conversion of its subjects (parish priests, vicars, deacons, religious, laity, among others). The second chapter deals with the formation of the New Parish as a path of maturity, in order to become a "community of communities", "family of families". Formation in the perspective of the Trinity, the disposition for dialogue, mission and communion are essential guidelines that shape the identity of the New Parish today, increasingly networked. The third chapter addresses the dimension of parish administration, an aspect through which the New Parish witnesses its spirituality and the values of the Kingdom of God. The New Parish is called to be open and transparent, with effective, Christian, planned and participatory management